The importance of proteinuria in preeclampsia and its predictive role in maternal and neonatal outcomes - Atakan Tanacan; Erdem Fadiloglu; Mehmet Sinan Beksac (Taylor & Francis Group, 2019)
Objective: To evaluate impact of 24-h proteinuria level in preeclampsia on maternal/perinatal outcomes. Methods: Singleton pregnancies with preeclampsia delivered after 24 weeks of gestation were included. Patients were divided into mild (0.3 to <2 g) (n=72), severe (2 to <5 g) (n=30), and massive (≥5 g) (n=24) proteinuria groups, and cut-off values of 24-h proteinuria for composite adverse maternal and neonatal outcomes were calculated. Results: Twenty-four hour  proteinuria level cut-offs for composite adverse outcomes were 3275 mg (72.2% sensitivity, 85.6% specificity) and 2395 mg (72.7% sensitivity, 78% specificity) respectively. Conclusion: Severe and massive proteinuria were related to poor maternal, perinatal, and neonatal outcomes.